Laboratory-confirmed Dengue in Children in Three Regional Hospitals in the Philippines in 2009−2010. Issue 11 (November 2015) - Capeding, Maria Rosario Z.; L'Azou, Maïna; Manalaysay, Michael; Vince-Woo, Cristina R.; Rivera, Religaya G.; Kristy Sy, Ava; Mercado, Edelwisa Segubre; Inobaya, Marianette T.; Tayag, Enrique G.
Abstract : Background: The burden of dengue is high in the Philippines but the prevalence of confirmed cases is unknown, and the disease is subject to underreporting because surveillance of suspected cases is passive. We conducted a prospective epidemiological study to estimate the proportion of laboratory-confirmed dengue among clinically suspected hospitalized cases in the pediatric wards of 3 regional hospitals in the Philippines and to describe the clinical and laboratory features, age distributions, case fatality rates and serotype distributions of these hospitalized cases. Methods: Patients ⩽18 years and hospitalized for suspected dengue were included if they had an axillary temperature ≥38°C for 2−7 days and 2 or more dengue-associated symptoms. Dengue infection was confirmed in acute blood samples by serotype-specific reverse transcription-polymerase chain reaction and IgM immunoassay. Results: We confirmed dengue infection in 1809 (86.1%) cases of 2103 suspected cases between November 2009 and November 2010. The 6- to 10-year-old age group had the highest proportion of cases overall (36.7%). Fever, anorexia, myalgia, abdominal pain and headache were the most common symptoms at admission. Hemorrhagic manifestations, signs of plasma leakage, thrombocytopenia and leucopenia were all significantly more common in confirmed than in nonconfirmed cases. Most cases (76.5%) developed dengue hemorrhagic fever or dengue shock syndrome, and the overall case fatality rate was 0.94%. Distributions of all 4 virus serotypes varied at each hospital. Conclusions: The clinical burden of pediatric dengue continues to be substantial in the Philippines. Most hospitalized cases of suspected pediatric dengue can be laboratory confirmed and most develop severe disease. Abstract : Supplemental Digital Content is available in the text.